Language teachers theoretical orientation and student language performance - Ravelo, Vengie M. (2008)
This research aimed to determine whether the teachers' theoretical orientation and classroom practices affect the student language performance in the National Achievement Test (NAT). Data were obtained through a three-part questionnaire administered to 36 language teachers from selected 12 high schools in the Caraga Region. Analysis revealed that teachers from high and moderate performing schools employed principled eclecticism while teachers from low performing schools dominantly employed the structural approach in language teaching. The teachers' theoretical orientation is correlated to their classroom practices, which means the higher the extent the teacher used the classroom practices, the greater the difference is in the NAT score of the students; while there was no significant difference between the teachers' theoretical orientation and the student NAT scores.